Fighting Political Gridlock : How States Shape Our Nation and Our Lives - Toscano, David J. (Book collections on Project MUSE., 2021)
"This book tracks state government policies topically, from health care to education to gun reform and more, making the case that true political change happens in state legislatures. Largely covering policy developments from the past ten years, with Virginia a prominent case study based on Toscano's own experiences, it is engaged in current topics, including COVID, and is a call to action"--